Transperitoneal Intervascular Approach for Repair of the Lumbar Spine - Geube, Alexander M.; Rios, Anthony; Tedesco, Janine A.; Landis, Gregg S. (International Journal of Angiology, 2016)
This report describes a novel anterior surgical approach to the midlumbar spine. A transperitoneal dissection separating the tissue planes between the infrarenal vena cava and abdominal aorta allows for ample exposure in the reconstruction of midlumbar vertebral body fractures.
Keywords: trauma; artery; repair; dissection